The Effectivity of Thymus vulgaris Extract on IL-1 Level and Bacterial Count in The Heart of Balb-c Mice Infected with MRSA - Galuh Yulieta Nitihapsari; Helmia Farida; Muchlis Achsan Udji Sofro (Journal of Biomedicine and Translational Research, 2021)
Background: The increasing phenomenon resistance of bacteria to various types of antibiotics, for example MRSA (Methicillin Resistant Staphylococcus aureus) became a serious problem. Over the last few decades S. aureus has become the dominant cause of endocarditis. MRSA data in Indonesia are still rarely reported. This has led to the importance of extracting natural substances that have anti-bacterial effects or that modulate immune response such as Thymus vulgaris (TV). It was hypothesized that TV can overcome MRSA infection by increasing IL-1, which is the initial cytokine in a natural immune response stimulated by the presence of S. aureus. Objective: This study was to investigate the effect of Thymus vulgaris extract on IL-1 and bacterial counts in the heart of balb-c mice infected with MRSA. Methods: There were 30 male Balb-c mice randomly divided into six groups. Group K (mice infected with MRSA without treatment),P1(mice treated with TV extract 7 days later infected with MRSA), P2(mice infected and treated with vancomycin), P3(mice infected and treated with TV+vancomycin extract), P4(mice infected and treated with amoxicillin), and P5 (mice infected and treated with TV extract+amoxicillin). IL-1 and bacterial count was assessed by ELISA and microbiological culture. Results: The result showed that there was a significant increase in IL-1 between groups (p=0.001).The median decrease in the bacterial count in the heart was 0 in almost treatment group except for P4 group which its median was 26.000 (p=0.161). The correlation between IL-1 levels and MRSA count in the heart had a weak negative correlation (r=-0.182). Conclusion: Thymus vulgaris extract was effective to  increase IL-1 levels significantly but was not proven to decrease MRSA count in the heart of balb-c mice.